HUBUNGAN KONSUMSI FAST FOOD DENGAN KEJADIAN BERAT BADAN LEBIH PADA REMAJA SEKOLAH MENENGAH ATAS DI KOTA BONE - Sakinah Amir; Syamsuriah Syamsuriah (Yayasan Nusantara Hasana Berdikari, 2026)
Changes in modern dietary patterns have led to an increase in fast food consumption among adolescents. Fast food is generally high in calories, saturated fat, and sugar, but low in fiber, which may contribute to an energy imbalance when consumed excessively. Consequently, excessive fast food consumption can increase the risk of overweight and obesity among adolescents. This study aimed to analyze the relationship between fast food consumption patterns and anthropometric status, specifically overweight and obesity, among high school students in Bone identified as having overnutrition tendencies. This study employed a quantitative design with a cross-sectional approach, in which all variables were observed simultaneously at a single point in time to assess the relationship between risk factors and their outcomes. Data were collected using a fast food consumption behavior questionnaire and anthropometric measurements to determine the nutritional status of the respondents. The study sample consisted of 49 respondents selected using a total sampling technique. Fast food consumption data were analyzed using SPSS Statistics, while anthropometric measurements were obtained using a microtoise and a weighing scale. The results of the chi-square test showed a statistically significant relationship between fast food consumption and anthropometric status (p = 0.041). These findings indicate that a higher frequency of fast food consumption is associated with an increased risk of overweight and obesity among adolescents